Semiphores in the Julius Maximilian University of Würzburg Space(s). The Educational Study - Majchrzak-Ptak, Kinga (Przegląd Badań Edukacyjnych (Educational Studies Review), 2021)
In the face of activities currently undertaken by different countries, including Poland, in the area of the so-called active policy of memory, research on commemoration is gaining importance. This research allows to discover the specific nature and the direction of the development of collective (non)memory frameworks, within which individual memory that is the basis for creating one’s own identity is constructed. Therefore, the subject of the paper is semiphores related to the past of Julius Maximilian University of Würzburg, i.e. objects that a given community recognizes as carriers of meanings and values that combine a semiotic dimension and a material dimension, and therefore objects that by definition should act as sites of memory. The paper presents the results of the ethnographic study, based on the analysis and interpretation of data collected thanks to (auto) observation and searching through the secondary sources, focused around the questions, such as: What is the nature of semiphores located at University of Würzburg? What is the importance of semiphores in architectural, social, cultural and educational spaces of University of Würzburg?, and allowing to conclude that e.g. the University of Würzburg is characterized by a responsible approach to commemorating past and constructing a framework for collective memory, but also that University of Würzburg memory is dominated by men, which has its educational implications.